Physport - Shores, Andrew; Hallaq, Tom (Kansas State University, 2017)
This project is developing a web-based, validated instrument to monitor, as the academic term progresses, student understanding of a wide range of introductory physics concepts. The distinguishing feature of the approach is a between-student testing mode of inquiry that allows assessment on a weekly timescale. The system rests upon a well-established body of research on student learning, forgetting, re-learning, and interference. Because large student numbers are necessary for statistical analysis, the system is particularly appropriate for the canonical "large lecture class" of 200-400 students (or larger). Rochester Institute of Technology is responsible for software development, Wabash College is overseeing question validation, and Emory University, Bucknell University, Rutgers University, and Johnson C. Smith University are beta testing the project.
Keywords: Sayre, Eleanor C.